Peran Pemerintah Banyuwangi terhadap Bangunan Pinggir Pantai - Khairinisa Nur Firdausyah; Warah Atikah (University of Jember, 2018)
Banyuwangi is a regency in East Java which focuses to transforming the regency into a tourism city, especially in the coastal tourism. As the development has sustained, it persuades investors to explore coastal tourism as a new business area. Consequently, the development of tourism in Banyuwangi regency generates new tourism places. On the other hand, however, there are further problems in areas of coastal tourism which were previously established. Watu Dodol Beach for instance, the beach has a lot of traditional outlets as business activities as results of coastal tourism with more than 37 years without any administrative documents. This paper is aimed to revisit the response of Government of Banyuwangi toward permanent buildings at beach’s borders according to administrative procedures according to Government Bylaw (Perda) Number 9 Year 2014 on Building. There are some critical notes to outline implications of such bylaw with the following dispute settlement. As mentioned by such bylaw, the absence of administrative documents on the establishment of outlets will impose the Government to issue reminder in writing, restrictions of building, postponement of activities, revocation of building permits (IMB), revocation of feasible function standard (SLF) and dismantling of buildings. As a result, the dispute settlement provided to address such administrative sanction comprises litigation and non-litigation processes. Keywords: Government of Banyuwangi, Building, Coastal Tourism